THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION, IN RESTAURANTS WOLFGANG'S STEAKHOUSE JAKARTA - Millenia, Cindy; Sukma, Rivera Pantro (Journal of Management and Leadership, 2022)
This study aims to analyze how Brand Image and Product Quality effect Customer Loyalty through Customer Satisfaction at Wolfgang's Steak House restaurant. The population in this study were customers of Wolfgang's Steak restaurant by taking samples through the purposive sampling method with certain considerations with transaction criteria more than 2 times a total of 204 respondents who became customers of Wolfgang's Steak House restaurant. The author uses a quantitative descriptive method, through SPSS 25 programming. It was found that brand image and product quality have a direct effect both on satisfaction and on loyalty; Brand image has a direct and indirect effect both on Customer Satisfaction and on Customer Loyalty; Product Quality has a direct effect on Customer Satisfaction and Customer Loyalty, but does not rely indirectly on loyalty with Customer Satisfaction mediation.